Application of directional derivative method to determine boundary of magnetic sources by total magnetic anomalies - Hang, Nguyen Thi Thu; Thanh, Do Duc; Minh, Le Huy (Vietnam Journal of Earth Sciences, 2017)
This paper presents the Directional Derivative method to determine location and boundaries of the magnetic directional structure sources through a new function DG (Directional Gradient - DG). Algorithm and computer program are made a code by Matlab language to attempt to calculate on 3D models in the compare with Horizontal derivative method (HG). A new function DG also applied to determine the boundary of magnetic sources by the total magnetic anomalies of Tuan Giao region. The result shows that with the application of new function DG, the boundaries of magnetic sources are exactly defined although they have a directional structure and small horizontal size. Moreover, because it does not depend on directions of magnetization, so in the computation, the transformation of the magnetic field to the pole can ignore, thus, reduce transient error. Alternatively, with the application of new function DG, the interferences in case the sources distributed close together are overcome. This usefulness affirms the possibility of application of the this method in the analysis and interpretation of magnetic data in Vietnam.ReferencesBhaskara Rao D. and N. Ramesh Babu, 1993. A fortran 77 computer program for tree dimensional inversion of magnetic anomalies resulting from multiple prismatic bodies, Computer & Geosciences, 19(8), 781-801.Beiki M., David A. Clark, James R. Austin, and Clive A. Foss, 2012. Estimating source location using normalized magnetic source strength calculated from magnetic gradient tensor data. Geophysics, 77(6), J23-J37. Blakely R.J., and R. W. Simpson, 1986. Approximating edges of source bodies from magnetic or gravity anomalies: Geophysics, 51, 1494 -1498. Blakely R.J., 1995. Potential theory in gravity and magnetic applications, Cambridge University Press. Cao Dinh Trieu, Pham Huy Long, 2002. Tectonic fault in Vietnam. Publisher of Science and Engineering. Debeglia N. and J. Corpel, 1997. Automatic 3-D interpretation of potential field data using analytic signal derivatives. Geophysics, 62, 87-96.Geological and Mineral resources map on 1:200,000. Seriesof Tay Bac, sheets of Muong Kha - Son La (F-48-XXV-F-48-XXVI), Phong Sa Ly - Dien Bien Phu (F-48-XIX-F-48-XX), Kim Binh - Lao Cai (F-48-VIII-F-48-XIV), 2005. Published and copyringt by Department of Geology and Minerals of Vietnam, Hanoi. Le Huy Minh, Luu Viet Hung, Cao Dinh Trieu, 2001. Some modern methods of the interpretation aeromagnetic data applied for Tuan Giao region. Vietnam Journal of Earth Sciences, 22(3), 207-216. Le Huy Minh, Luu Viet Hung, Cao Dinh Trieu, 2002. Using the maximum horizontal gradient vector to interpret magnetic and gravity data in Vietnam. Vietnam Journal of Earth Sciences, 24(1), 67-80. Nabighian M.N., 1972. The analytic signal of two-dimensional magnetic bodies with polygonal cross-section: Its properties and use of automated anomaly interpretation: Geophysics, 37, 507-517. Nabighian M.N., 1974. Additional comments on the analytic signal of two-dimensionalmagnetic bodies with polygonal cross-section. Geophysics, 39, 85-92. Roest W. R., J. Verhoef and  M. Pilkington, 1992. Magnetic interpretation using the 3-D analytic signal: Geophysics, 57, 116-125. Vo Thanh Son, Le Huy Minh, Luu Viet Hung, 2005. Three-dimensional analytic signal method and its application in interpretation of aeromagnetic anomaly maps in the Tuan Giao region. Proceedings of the 4th geophysical scientific and technical conference of Vietnam, Publisher of Science and Engineering 2005. Vo Thanh Son, Le Huy Minh, Luu Viet Hung, 2005. Determining the horizontal position and depth of the density discontinuties in Red River Delta by using the vertical derivative and Euler deconvolution for the gravity anomaly data, Journal of Geology, Series A, 287(3-4), 39-52.Vo Thanh Son, et al., 2007. Determining the location and depth of contrast magnetic boundaries by using 3D analytics signal method and higher derivatives. Proceeding of the 5th geophysical scientific and technical conference of Vietnam.